Upaya Meningkatkan Derajat Kesehatan Gigi dan Mulut Melalui Pelatihan Kader Posyandu Di Kecamatan Marga Kabupaten Tabanan Tahun 2018 - Ni wayan Arini; Ni Ketut Ratmini; I Nyoman Wirata; Ni Made Sirat (Jurnal Pengabmas Masyarakat Sehat, 2019)
Dental health problems in Indonesia are still a matter that still needs serious attention because the prevalence of caries reaches 60-80% of the population, and ranks 6th as the most common disease. Dental and oral health services, especially aimed at groups prone to dental health problems, namely pre-school children and elementary school children. The purpose of the activity was to improve the degree of dental and oral health of visitors to posyandu in Marga sub-district. This community service was carried out on Posyandu paramedic assistance in Kukuh village, Kec. Marga, Kab. Tabanan. Implementation of activities in the form of training with lecture methods, question and answer and simulation. The targets were 35 Posyandu paramedic assistance. The results of the training were obtained by the level of knowledge of paramedic assistance about oral and dental health as much as 62.9%, all paramedic assistance (100%) were skilled in brushing their teeth in the right way and early detection of cavities.Keywords: training, paramedic assistance, oral and dental health